2022
DOI: 10.1186/s12939-022-01650-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in physiological risk biomarkers and the role of lifestyles among Russians aged 35-69 years

Abstract: Background Socioeconomic inequalities in cardiovascular (CVD) health outcomes are well documented. While Russia has one of the highest levels of CVD mortality in the world, the literature on contemporary socio-economic inequalities in biomarker CVD risk factors is sparse. This paper aims to assess the extent and the direction of SEP inequalities in established physiological CVD risk biomarkers, and to explore the role of lifestyle factors in explaining SEP inequalities in physiological CVD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Therefore, the associations of these socio-demographic characteristics with LGSI were likely mediated by the studied lifestyle and cardiometabolic variables. Similarly, a number of previous studies demonstrated associations of higher CRP levels with lower levels of education and income, but health behaviors and metabolic parameters explained the major part of these differences [23,[63][64][65].…”
Section: Socio-demographic Correlatesmentioning
confidence: 73%
“…Therefore, the associations of these socio-demographic characteristics with LGSI were likely mediated by the studied lifestyle and cardiometabolic variables. Similarly, a number of previous studies demonstrated associations of higher CRP levels with lower levels of education and income, but health behaviors and metabolic parameters explained the major part of these differences [23,[63][64][65].…”
Section: Socio-demographic Correlatesmentioning
confidence: 73%